Improving hospital-based trauma care for road traffic injuries in Malawi - Chokotho, Linda (World J Emerg Med, 2017)
BACKGROUND: The mortality rate from road traffic injuries has increased in sub-Saharan Africa as the number of motor vehicles increase. This study examined the capacity of hospitals along Malawi’s main north-south highway to provide emergency trauma care. METHODS: Structured interviews and checklists were used to evaluate the infrastructure, personnel, supplies, and equipment at all four of Malawi’s central hospitals, ten district hospitals, and one mission hospital in 2014. Most of these facilities are along the main north-south highway that spans the country. RESULTS: Between July 2013 and March 2014, more than 9 200 road traffic injuries (RTIs) and 100 RTI deaths were recorded by the participating hospitals. All of the hospitals reported staff shortages, especially during nights and weekends. Few clinicians had completed formal training in emergency trauma management, and healthcare workers reported gaps in knowledge and skills, especially at district hospitals. Most central hospitals had access to the critical supplies and medications necessary for trauma care, but district hospitals lacked some of the supplies and equipment needed for diagnosis, treatment, and personal protection. CONCLUSION: The mortality and disability burden from road traffic injuries in Malawi (and other low-income countries in sub-Saharan Africa) can be reduced by ensuring that every central and district hospital has a dedicated trauma unit with qualified staff who have completed primary trauma care courses and have access to the equipment necessary to save lives.